The Family Support and ART Adherence among PLHIV in Indonesia: A Systematic Review - Satria Akbar Putra Asmara; Naura Athiya; Muhammadiena Ramadhannisa Wijayanto; Titik Kuntari (Griya Widya: Journal of Sexual and Reproductive Health, 2026)
Background: Adherence to antiretroviral therapy (ART) is a key determinant of treatment success for people living with HIV (PLHIV) in Indonesia. Family support is thought to play a crucial role in enhancing this adherence, yet existing research findings remain inconsistent. Objective: This literature review aims to synthesize recent evidence on the relationship between family support and ART adherence among PLHIV in Indonesia. Method: A systematic review was conducted by searching articles in PubMed, Google Scholar, and Science Direct (publication range 2021-2025). Nine cross-sectional studies meeting the inclusion criteria were synthesized using the PRISMA method. Result: Seven out of nine studies (77.8%) reported a statistically significant relationship between family support and improved ART adherence. Dimensions of emotional, instrumental, and informational support were consistently associated with positive outcomes. Inconsistencies in findings from some studies were suspected to be related to variations in measuring the "family support" construct and socio-cultural contexts. Implication: The predominant evidence supports the positive role of family support in ART adherence in Indonesia. Adherence promotion programs are recommended to integrate family-involved interventions, considering multidimensional and context-specific measurement approaches.